Adaptive gamification in e-learning based on students' learning styles. Issue 4 (19th May 2021) - Hassan, Muhammad Awais; Habiba, Ume; Majeed, Fiaz; Shoaib, Muhammad
ABSTRACT: With the removal of the barriers of time and distance, E-learning platforms have attracted millions of learners, but these platforms are experiencing a significant drop-out ratio. One of the primary reasons for this problem is the lack of motivation among the learners because of the similar learning experience provided to them despite their varying learning styles. Different researchers have introduced gamification as a solution for students' engagement. The technique has improved engagement levels a bit, but it is not as useful as it was expected to be. One of the primary problems with gamification elements is their inability to induce intrinsic motivation among learners. To target this issue, we have proposed a framework that identifies the learning style of students based on their interactions with the system and provides an adaptive gamification experience according to their identified learning dimensions. The results of the experiments show that the motivation of learners increases by 25%, and the drop-out ratio is reduced by 26%.